2020
DOI: 10.3390/cells9051094
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Crosstalk between AR3 and E2F1 in Drug Resistance in Prostate Cancer Cells

Abstract: Background: Drug resistance is one of the most prevalent causes of death in advanced prostate cancer patients. Combination therapies that target cancer cells via different mechanisms to overcome resistance have gained increased attention in recent years. However, the optimal drug combinations and the underlying mechanisms are yet to be fully explored. Aim and methods: The aim of this study is to investigate drug combinations that inhibit the growth of drug-resistant cells and determine the underlying mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…This suggested that ARv7 might be involved in the cross-resistance between ENZ and ABI. Although ARv7-positive patients showed much worse treatment responses to NHT (Armstrong et al, 2020;Wang et al, 2020a;Wang et al, 2020b), the clinical data analysis demonstrated that these patients could significantly benefit from taxane chemotherapy, which was possibly related to the higher activity of the E2F1/AR3 feed-forward loop (Xu et al, 2020). The CXCR7-JAK2/STAT1 signaling pathway, as an independent AR bypass pathway, may also participate in resistance to androgen target therapy.…”
Section: Discussionmentioning
confidence: 98%
“…This suggested that ARv7 might be involved in the cross-resistance between ENZ and ABI. Although ARv7-positive patients showed much worse treatment responses to NHT (Armstrong et al, 2020;Wang et al, 2020a;Wang et al, 2020b), the clinical data analysis demonstrated that these patients could significantly benefit from taxane chemotherapy, which was possibly related to the higher activity of the E2F1/AR3 feed-forward loop (Xu et al, 2020). The CXCR7-JAK2/STAT1 signaling pathway, as an independent AR bypass pathway, may also participate in resistance to androgen target therapy.…”
Section: Discussionmentioning
confidence: 98%
“…In this context, Liu et al proved that AF (1 µM) promoted androgen receptor protein degradation and inhibited androgen receptor transcription in two androgen receptor‐positive cell lines, LNcap and 22RV1 125 . Xu et al demonstrated that the combination of enzalutamide (ENZ) and docetaxel (DTX) effectively inhibited the growth of prostate cancer cells that are resistant to either single drug 126 . Thus, the authors generated a cell line resistant to both DTX and ENZ and demonstrated that AF could overcome resistance by inhibiting the growth of these drug‐resistant prostate cancer cells both in vitro and in vivo.…”
Section: Af Repurposing In Cancer Therapymentioning
confidence: 99%
“… 125 Xu et al demonstrated that the combination of enzalutamide (ENZ) and docetaxel (DTX) effectively inhibited the growth of prostate cancer cells that are resistant to either single drug. 126 Thus, the authors generated a cell line resistant to both DTX and ENZ and demonstrated that AF could overcome resistance by inhibiting the growth of these drug‐resistant prostate cancer cells both in vitro and in vivo.…”
Section: Af Repurposing In Cancer Therapymentioning
confidence: 99%
“…Yang et al demonstrated that high expression of E2F1 is associated with unfavorable prognosis in PCa cells ( 32 ). The study by Xu et al showed that E2F1 was markedly up in cancer and plays a key role in cellular inhibition when it is down-regulated ( 33 ). Qi et al showed that in PCa cells, E2F1 participates in epithelial mesenchymal transition (EMT) ( 34 ).…”
Section: Discussionmentioning
confidence: 99%